Improved Polar selective decoding and forwarding cooperation - Qichao SUN; Jianrong BAO; Chao LIU; Bin JIANG; Fang ZHU; Jianhai HE (Dianxin kexue)
An improved Polar selective decoding and forwarding (IPSDF) scheme based on cooperative threshold de-cision was proposed.Firstly,a new construction of Polar codes according to the fading channel state information (CSI) was proposed.Then,a relay with best CSI was selected from the candidate relay set as the best relay.In addition,the proposed Polar codes were introduced into the cooperative communication system,to get coding gain and reduce the complex of encoding and decoding.Simulation results show that the proposed Polar codes achieve about 0.3 dB gain at bit-error-rate (BER) of 10−3.And using a classic multi-relay cooperative model,the proposed scheme achieves about 0.8 dB and 1.3 dB gain at BER of 10−3,when compared with those the existing DF Polar+ and network Polar coded coopera-tion scheme.Therefore,the IPSDF scheme can be used to improve BER performance in a multi-relay cooperative system and it is quite suitable for heterogeneous network applications in cooperative communication.